Lao People's Democratic Republic : Joint Staff Assessment of the Poverty Reduction Strategy Paper Preparation Status Report. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2003)
The Joint Staff Assessment (JSA) of the Poverty Reduction Strategy Paper Preparation Status Report for the Lao People's Democratic Republic was prepared by the staff of both the World Bank and IMF. The JSA evaluates the strengths and weaknesses of a country's poverty reduction objectives and strategies, and considers whether the PRSP or IPRSP provides a sound basis for concessional assistance from the Bank and IMF, as well as for debt relief under the Enhanced Heavily Indebted Poor Countries (HIPC) Debt Initiative.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: CR; Draft NPEP; Government; ISCR; NPEP Monitoring; Lao People's Democratic Republic